Enantioselective (3+2)-Annulation of β-Keto Esters with Azoalkenes towards Bicyclic Dihydropyrroles via Cooperative Palladium and Brønsted Acid Catalysis - Friedmann, Till; Mireles-Chávez, Daniel A.; Walter, Frederik L.; Schneider, Christoph (Synlett, 2023)
A cooperative catalytic process through palladium and Brønsted acid activation is developed for the conjugate addition of cyclic β-keto esters to azoalkenes directly followed by hemiaminal formation upon cyclization. This transformation is enabled by utilizing chiral Pd-aqua complexes as combined Brønsted acid–base catalysts. Thus, bicyclic and highly functionalized dihydropyrroles with two contiguous quaternary stereogenic centers are formed in excellent yields as single diastereomers and with exceptional enantioselectivity.
Keywords: asymmetric catalysis; azoalkenes; (3+2) cycloaddition; cooperative catalysis; heterocycles; Pd-aqua complexes; Pd-enolates